2017
DOI: 10.18203/2320-1770.ijrcog20173718
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices among healthcare providers on cervical cancer, human papilloma virus and it’s vaccine at ESI PGIMSR, MGM Hospital Parel Mumbai, India

Abstract: Background: Cervical cancer is the second most common cause of cancer in females Worldwide and nearly 85% of the cervical cancer cases are diagnosed in developing countries. The health care providers can play an important role in promoting cervical cancer screening and knowledge about HPV vaccination. So this study was conducted to assess the knowledge, attitude and practices regarding cervical cancer screening and HPV vaccination and to analyze the factors influencing the knowledge about HPV vaccination, amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Even Gedam et al reported that only 33 per cent of the nurses had received education on cervical cancer and HPV in the past. 14 Despite continued training on STI/RTI being provided to healthcare professional, only about two thirds of the ASHAs and BHWs in the present study were aware of 'multiple sexual partners' and only about half of the PHWs knew that 'unprotected sex' as risk factors for cervical cancer. Researchers have reported similar level of awareness among community women of North Bengal and Tripura and HCP of Chennai Corporation about 'multiple sexual partners' as risk factor.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Even Gedam et al reported that only 33 per cent of the nurses had received education on cervical cancer and HPV in the past. 14 Despite continued training on STI/RTI being provided to healthcare professional, only about two thirds of the ASHAs and BHWs in the present study were aware of 'multiple sexual partners' and only about half of the PHWs knew that 'unprotected sex' as risk factors for cervical cancer. Researchers have reported similar level of awareness among community women of North Bengal and Tripura and HCP of Chennai Corporation about 'multiple sexual partners' as risk factor.…”
Section: Discussioncontrasting
confidence: 54%
“…Healthcare professionals had pretty good awareness. 9,14,21,22 Awareness regarding Sampoorna clinic providing screening and vaccination facility for cervical cancer was also found to be very low in the present study. 23…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The frequency of effective HPV vaccine uptake was one of the lowest in the recent literature (0.8%), as found in low income settings [40]. It is usually higher in high income environment [35,40].…”
Section: Attitudes and Effective Hpv Vaccination Uptakementioning
confidence: 99%